Motivasi Belajar pada Mata Pelajaran Akidah Akhlak dengan Menggunakan Metode PAKEM - Rismiyati, Eka; Madi, Madi; La Jusu, La Jusu (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to improve the learning motivation of Grade VII students at MTS Waburense in the subject of Akidah Akhlak by implementing an Active, Creative, Effective, and Joyful learning method. The study adopts the classroom action research model by Kemmis and McTaggart. Data were collected through observation, tests, and documentation.The results indicate an increase in student motivation and learning outcomes. In the pre-cycle stage, the average student score was 50.83, with a mastery level of only 29.16% (7 students achieved the standard). In Cycle I, the average score rose to 69.16, with 62.5% of students (15 students) achieving learning mastery. In Cycle II, the average score further increased to 82.5, with 87.5% of students (21 students) meeting the learning mastery criteria. These findings demonstrate that the application of an active and enjoyable learning method can significantly enhance student motivation and academic performance. Therefore, this method is recommended as an effective strategy to improve student engagement and achievement.